Legal incentives in the contractual regulation of marital relations - O. H. Bortnik; T. V. Stepanenko (Law and Safety)
The aim of the work is to establish the role of legal incentives in the mechanism of legal regulation of marital relations. In the course of the research the special role of personal intangible assets as the basis of family relations was established, which determines the choice of the optimal model of legal regulation of such relations. It is argued that the satisfaction of intangible needs (spiritual, moral and ethical, psycho-emotional security, physical development) determines the legally protected interests of marital and family members, who often face obstacles due to individual psychological characteristics of the spouses, interrelated with their property rights. It is emphasized that in establishing the legal regime, which should facilitate the choice of active lawful behavior, it is advisable to resort to means of encouraging socially active lawful behavior such as legal incentives. The study is based on a systems approach. Given the purpose of the study, methods d that generally allowed to determine the optimal type of legal understanding, which solved the problem of finding a tool of interpretationwere use: analysis and synthesis, induction and deduction, formal law and comparative law and other methods. Arguments are made in favor of the opinion that contractual regulation of personal non-property legal relations of spouses, which is not traditionally in practice, in comparison with regulation of parental personal non-property legal relations, does not contradict the provisions of current legislation and the essence of legal relations, and from the point of view of the legal impact of informational and psychological nature contribute to the understanding and social activity of the subjects of marital and family relations. It is concluded that the opportunity for a person to obtain legal guarantees for the exercise of personal non-property rights in marriage is an important legal incentive to use the contractual method of regulating marital relations. It is through legal incentives that are reflected in the mechanism of legal regulation through subjective rights, and the right to behave in individual ways, which are determined by the person, must be influenced. Self-regulation of relevant legal relations through the definition of ways of exercising subjective law allows to balance the needs, subjective rights and legal obligations of each spouse, as well as spouses as parents, to protect their legally protected interests related to the exercise of personal non-property rights as parents, to guarantee the exercise of the rights of the child (children) in accordance with its best interests. The results of the study can be used in further theoretical research to determine the optimal mechanisms of legal regulation of marital relations between parents and spouses, and in law enforcement activities of legal practitioners in developing the terms of contracts concluded in the field of marital and family relations.